Electrolyte membrane and method for manufacturing same
By filling the polyolefin microporous membrane with low EW perfluorosulfonic acid polymer, the problem of insufficient proton conductivity and mechanical strength of the electrolyte membrane is solved, and efficient fuel cell performance under low humidity conditions is achieved, which simplifies the system structure and reduces costs.
Patent Information
- Application Number
- CN202510683809.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-07-25
- Filing Date
- 2017-05-31
- Publication Date
- 2025-07-08
AI Technical Summary
The existing electrolyte membranes have shortcomings in proton conductivity, mechanical strength and preventing fuel gas transmission, especially in low humidity conditions, and require additional humidification and cooling devices, which increase the cost and complexity of fuel cell systems.
The low-EW perfluorosulfonic acid polymer is used to fill a specific polyolefin microporous membrane to form a composite film. By adjusting the pore size, porosity and surface free energy, the high proton conductivity and mechanical strength of the electrolyte membrane are achieved, avoiding the need for humidification and cooling devices.
Maintaining high proton conductivity under low humidity conditions, the thin-film electrolyte membrane improves the efficiency and stability of fuel cells, reduces the demand for accessories, and reduces system costs.
Smart Images

Figure CN120280523A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese Patent Application No. 201780045290.3 (PCT Application No. PCT / JP2017 / 020368) with the filing date of May 31, 2017 and the invention title of "Electrolyte Membrane and Method for Producing the Same". Technical Field
[0002] The present invention relates to a pore-filled membrane type electrolyte membrane suitable for use in a polymer electrolyte fuel cell, water electrolysis, sodium electrolysis, etc., and a method for producing the same. Background Art
[0003] In recent years, there has been an increasing demand for improving the performance of electrolyte membranes, particularly polymer electrolyte membranes. For example, the following system has attracted attention as a very clean energy system that does not generate carbon dioxide. In this system, water is electrolyzed using renewable energy such as sunlight and wind power to produce hydrogen, and the produced hydrogen is stored. At a location where power is needed and at a time when it is needed, the hydrogen is supplied to a fuel cell for power generation. Here, a method of water electrolysis in which an anode and a cathode are separated by an electrolyte membrane during water electrolysis, protons generated at the anode move through the electrolyte membrane to the cathode, and hydrogen is obtained by combining with electrons at the cathode is known. The reaction formulas at each electrode are as follows.
[0004] · Anode: H2O → 1 / 2O2 + 2H + + 2e -
[0005] · Cathode: 2H + + 2e - → H2
[0006] On the other hand, in a fuel cell, protons generated in the hydrogen oxidation reaction at the negative electrode (anode) move through the electrolyte membrane to the positive electrode (cathode), and water is generated by an oxygen reduction reaction at the positive electrode to generate power. The reaction formulas at each electrode are as follows.
[0007] · Negative electrode: H2 → 2H + + 2e -
[0008] · Positive electrode: 1 / 2O2 + 2H + + 2e - → H2O
[0009] As can be seen from the above operating principles, improving the proton conductivity of the electrolyte membrane is a common issue in both the water electrolysis method and fuel cells. To improve the proton conductivity of the electrolyte membrane, measures such as reducing the membrane thickness of the electrolyte membrane and decreasing the dry mass per 1 equivalent of ion exchange groups of the electrolyte polymer (equivalent weight: EW) can be taken. However, from the viewpoints of the strength required as a separator between electrodes and preventing the permeation of fuel gases such as hydrogen (crossing phenomenon), there are natural limits to thinning the film. In addition, reducing the EW also has the following limitations depending on the application: the ratio of the skeleton part of the electrolyte polymer decreases and it becomes difficult to maintain a solid membrane; also, in fuel cells, in addition to the water generated at the positive electrode, a part of the moisture on the negative electrode side moves together with protons through the electrolyte membrane to the positive electrode side, easily causing a flooding phenomenon where the air inlet on the positive electrode side is blocked by water, and so on.
[0010] In addition, since protons must be hydrated in order to move in the electrolyte membrane, fuel cells need to be equipped with a humidifying device for replenishing moisture to the negative electrode side that gradually loses moisture during operation, and the humidity is adjusted to about 90%. In addition, in view of this "using water" condition, a cooling device for maintaining the operating temperature of the fuel cell at about 60 to 80°C is also required. The installation of these auxiliary devices becomes an obstacle to reducing the overall cost of the fuel cell system and improving efficiency. Therefore, it is desired to develop an electrolyte membrane that can be used under non-humidifying and medium-high temperature conditions.
[0011] Examples of polymer electrolytes for fuel cells are as follows: By making the internal space (voids) of a polymer porous membrane contain a polymer electrolyte, an improvement in mechanical strength that cannot be achieved by the electrolyte itself is achieved (Patent Document 1). In addition, a porous substrate suitable for holding a polymer electrolyte in a polyethylene porous membrane has been proposed (Patent Document 2). In addition, there is a prior art in which a network structure of a porous film of ultra-high molecular weight polyolefin incorporates and contains an ion exchange resin to provide an electrolyte film with excellent mechanical strength (Patent Document 3). In addition, there is also a prior art in which an ion conductor is incorporated and contained in a solid polymer porous membrane by utilizing capillary condensation to provide a thin film electrolyte with excellent mechanical strength (Patent Document 4). However, these existing electrolyte membranes are still insufficient for solving the above problems.
[0012] Prior Art Documents
[0013] Patent Documents
[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 2005-166557
[0015] Patent Document 2: Japanese Patent Application Laid-Open No. 2011-241361
[0016] Patent Document 3: Japanese Patent Laid-Open No. 64-22932
[0017] Patent Document 4: Japanese Patent Laid-Open No. 1-158051 Summary of the Invention
[0018] Problems to be Solved by the Invention
[0019] Therefore, an object of the present invention is to provide an electrolyte membrane with high proton conductivity that can fundamentally overcome the above various problems.
[0020] Means for Solving the Problems
[0021] The inventors of the present application conducted in-depth research to solve the above problems and found that by using a composite film formed by filling an electrolyte polymer with a low EW into a specific polyolefin microporous membrane, the above various problems can be fundamentally solved. That is, the present invention provides the following constitution.
[0022] [1] An electrolyte membrane comprising a composite membrane, the composite membrane comprising:
[0023] A polyolefin microporous membrane having an average pore diameter of 1 to 1000 nm, a porosity of 50 to 90%, and capable of impregnating a solvent having a surface free energy of 28 mJ / m at 20°C; and 2 and
[0024] An electrolyte containing a perfluorosulfonic acid polymer with an EW of 250 to 850, the electrolyte being filled in the pores of the polyolefin microporous membrane, wherein,
[0025] the composite membrane has a film thickness of 1 to 20 μm.
[0026] [2] The electrolyte membrane according to [1] above, wherein the average pore diameter is 5 to 100 nm.
[0027] [3] The electrolyte membrane according to [1] or [2] above, wherein the porosity is 50 to 78%.
[0028] [4] The electrolyte membrane according to any one of [1] to [3] above, which comprises a polyolefin microporous membrane capable of impregnating a solvent having a surface free energy of 33 to 37 mJ / m at 20°C. 2
[0029] [5] The electrolyte membrane according to any one of [1] to [4] above, wherein the electrolyte contains a perfluorosulfonic acid polymer with an EW of 450 to 650.
[0030] [6] The electrolyte membrane according to any one of [1] to [5] above, wherein the composite membrane has a film thickness of 5 to 12 μm.
[0031] [7] The electrolyte membrane according to any one of [1] to [6] above, wherein the electrolyte membrane is used as an electrolyte membrane for a polymer electrolyte fuel cell, electrolysis of water, or sodium electrolysis.
[0032] [8] A method for manufacturing an electrolyte membrane, which is a method for manufacturing the electrolyte membrane according to any one of [1] to [7] above, and the manufacturing method comprises the following steps:
[0033] A step of impregnating the following solution into a polyolefin microporous membrane, wherein the average pore diameter of the polyolefin microporous membrane is 1 to 1000 nm, the porosity is 50 to 90%, and it can impregnate a solvent with a surface free energy of 28 mJ / m 2 or more at 20°C. The solution is obtained by dissolving an electrolyte of a perfluorosulfonic acid polymer containing EW250 to 850 in the solvent;
[0034] A step of drying the polyolefin microporous membrane after the impregnation step to remove the solvent; and
[0035] A step of annealing the polyolefin microporous membrane after the removal step.
[0036] Effects of the Invention
[0037] According to the present invention, an electrolyte membrane that can exhibit high proton conductivity even at low humidity can be obtained. In addition, combined with a relatively thin film thickness, an electrolyte membrane that is particularly advantageous for use in polymer electrolyte fuel cells can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 ] A graph for comparing the proton conductivity by AC impedance method (In-plane) for an electrolyte using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0039] Figure 2 ] A graph for comparing the relative humidity dependence of the proton conductivity for a membrane electrode assembly (MEA) using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0040] Figure 3 ] A graph for comparing the current density dependence of the cell voltage at a humidity of 30% for an MEA using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0041] Figure 4 This is a graph comparing the current density dependence of the cell voltage at a humidity of 20% for the MEA using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0042] Figure 5 This is a graph comparing the current density dependence of the cell voltage at a humidity of 10% for the MEA using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0043] Figure 6 This is a graph comparing the results of the hydrogen crossover test for the MEA using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0044] Figure 7 This is a graph comparing the current density dependence of the cell voltage at a temperature of 80 - 100 °C for the MEA using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane.
[0045] Figure 8 This is a graph comparing the proton conductivity by in-plane AC impedance measurement for the electrolyte using the polyolefin microporous membrane of the present invention and a conventional electrolyte membrane. Detailed Description of the Invention
[0046] The present invention is based on the insight that a low-EW electrolyte polymer can be easily filled into a specific polyolefin microporous membrane. It is generally difficult to impregnate and fill a highly hydrophilic low-EW electrolyte polymer into the pores of a polyolefin microporous membrane that is originally highly hydrophobic. However, the inventors of the present application focused on the surface free energy of the solvent used in the solution of the electrolyte polymer and conducted research. As a result, it was found that even a low-EW electrolyte polymer with an EW in the order of 500 can be dissolved in a solvent having a specific surface free energy to form a solution, and thus can be easily impregnated and filled into the polyolefin microporous membrane, exhibiting a relatively high proton conductivity as a whole.
[0047] Hereinafter, the embodiments of the present invention will be described in sequence. However, these descriptions and examples are examples of the present invention and do not limit the scope of the present invention. It should be noted that throughout this specification, when a numerical range uses "~", each numerical range includes its upper and lower limits. In addition, with respect to the polyolefin microporous membrane, the so-called "length direction" or "MD" refers to the long strip direction of the polyolefin microporous membrane manufactured in a long strip shape, and the so-called "width direction" or "TD" refers to the direction orthogonal to the length direction of the polyolefin microporous membrane.
[0048] [Polyolefin Microporous Membrane]
[0049] The average pore diameter of the polyolefin microporous membrane used in the present invention is 1 to 1000 nm, the porosity is 50 to 90%, and it can be impregnated with a solvent having a surface free energy of 28 mJ / m at 20 °C. 2 or more.
[0050] (Average pore diameter)
[0051] The average pore diameter of the polyolefin microporous membrane of the present invention is 1 to 1000 nm. When the average pore diameter is 1000 nm or less, even for a microporous membrane with a high porosity, the mechanical strength of the polyolefin microporous membrane is still good, and the operability is also improved, which is preferable in this regard. In addition, at a constant porosity, the smaller the average pore diameter, the higher the frequency of pores present in the microporous membrane. Therefore, the electrolyte compound can be uniformly filled into the entire polyolefin microporous membrane. In addition, since the frequency of pores on the surface of the microporous membrane increases, the penetration of the electrolyte compound solution using a solvent with a higher surface free energy becomes good. From this perspective, the average pore diameter of the polyolefin microporous membrane is preferably 500 nm or less, more preferably 100 nm or less, further preferably 50 nm or less, particularly preferably 45 nm or less, and even more preferably 40 nm or less. On the other hand, when the average pore diameter is 1 nm or more, the penetration rate of the solvent with a high surface free energy increases. From this perspective, the average pore diameter of the polyolefin microporous membrane is preferably 5 nm or more, more preferably 10 nm or more.
[0052] Here, the average pore diameter of the polyolefin microporous membrane can be measured by the measurement method described in the examples below.
[0053] (Porosity)
[0054] The porosity of the polyolefin microporous membrane of the present invention is 50 to 90%. When the porosity is 50% or more, it is preferable in terms of increasing the filling rate of the electrolyte compound and being able to fully exhibit the original performance of the electrolyte compound. In addition, it is preferable in terms of the solution dissolved with the electrolyte compound being easily permeable through the microporous membrane and the impregnation rate being accelerated. From this perspective, the porosity of the polyolefin microporous membrane is preferably 55% or more, more preferably 60% or more. On the other hand, when the porosity is 90% or less, it is preferable in terms of the mechanical strength of the polyolefin microporous membrane becoming good and the operability also being improved. From this perspective, the porosity of the polyolefin microporous membrane is preferably 85% or less, more preferably 78% or less, particularly preferably 75% or less, and even more preferably 66% or less.
[0055] Here, the porosity (ε) of the polyolefin microporous membrane can be measured by the measurement method described in the examples below and calculated by the following formula.
[0056] ε(%) = {1 - Ws / (ds·t)} × 100
[0057] Ws: Unit area weight of the polyolefin microporous membrane (g / m 2 )
[0058] ds: True density of the polyolefin (g / cm 3 )
[0059] t: Membrane thickness of the polyolefin microporous membrane (μm)
[0060] (Surface free energy of the solvent that can be impregnated)
[0061] The polyolefin microporous membrane of the present invention can be impregnated with a solvent having a surface free energy of 28 mJ / m 2 or more. In the specification of the present application, the surface free energy of the solvent refers to the measured value at 20°C. In addition, the so-called "can be impregnated" means that the solvent can spontaneously penetrate into the pores when it is only in contact with the microporous membrane without performing a forced filling treatment based on pressure or decompression.
[0062] Generally, the polyolefin microporous membrane has a low surface free energy and high waterproofness. Therefore, it is not easy to wet a hydrophilic liquid with a high surface free energy, and it is difficult to fill a hydrophilic substance such as an electrolyte compound into the pores of the microporous membrane. Methods for surface-modifying the polyolefin microporous membrane to make it hydrophilic (hydrophilic treatment) are well known, but there are cases where impurity components remain in the microporous membrane in chemical surface treatment (treatment using surfactants, etc.), which damages the desired performance. In addition, physical surface treatment (plasma treatment, corona treatment, etc.) has the disadvantage of damaging the microporous membrane and reducing its physical strength, and cannot be used for electrolyte membranes that especially require thinning.
[0063] On the other hand, when the surface free energy of the solvent is 28 mJ / m 2 or more, it is preferable in terms of being able to increase the dissolution concentration of the electrolyte compound in the solvent and thus being able to improve the efficiency of filling the electrolyte compound into the microporous membrane. However, heretofore, especially for a polyolefin microporous membrane that has not been subjected to hydrophilic treatment, it has been impossible to impregnate a solvent (liquid) having a surface free energy of 28 mJ / m 2 or more without performing a forced filling treatment based on pressure or decompression.
[0064] The upper limit of the surface free energy of the solvent is the value at which it can no longer be impregnated into the polyolefin microporous membrane that satisfies the above average pore diameter and porosity, and is approximately 38 mJ / m 2From the aspect of improving the affinity between the solvent of the electrolyte compound with enhanced dissolution hydrophilicity and the polyolefin microporous membrane, and making the solution containing the electrolyte compound easily permeate through the microporous membrane, it is preferable that the surface free energy of the solvent is relatively low. Thus, for the surface free energy of the solvent in the present invention, there is a trade-off relationship between the electrolyte solution concentration and the impregnability with respect to the microporous membrane. In individual specific applications, it can be appropriately set within the range of 28 mJ / m 2 or more, preferably 33 mJ / m 2 or more, more preferably 35 mJ / m 2 or more, and 38 mJ / m 2 or less, preferably 37 mJ / m 2 or less, more preferably 36.5 mJ / m 2 or less.
[0065] As a method for adjusting the surface free energy of the solvent, it is possible to mix organic solvents such as alcohols (methanol, ethanol, isopropyl alcohol, tert-butanol, etc.), ethylene glycol, tetrahydrofuran, acetone, methyl ethyl ketone, dimethylformamide, and triethylamine in water. For reference, regarding the surface free energy at 20 °C, water is 72.8 mJ / m 2 , ethanol is 22.39 mJ / m 2 , 1-propanol is 23.71 mJ / m 2 , 1-butanol is 25.28 mJ / m 2 , hexane is 18.40 mJ / m 2 , perfluorohexane is 11.91 mJ / m 2 .
[0066] (Film thickness)
[0067] For the polyolefin microporous membrane of the present invention, the thickness of the composite membrane obtained by filling the pores with an electrolyte as described later is 1 to 20 μm. When the film thickness of the composite membrane is 1 μm or more, it is easy to obtain sufficient mechanical strength as an electrolyte membrane. In addition, the operability during the processing of the polyolefin microporous membrane is improved, and it can be stably transported during the processing of impregnating the electrolyte solution. Therefore, it is preferable. From such a viewpoint, the film thickness of the composite membrane is preferably 3 μm or more, particularly preferably 4 μm or more, and further preferably 5 μm or more. On the other hand, when the thickness is 20 μm or less, the time required for impregnating the polyolefin microporous membrane with the electrolyte solution can be shortened, and the electrolyte compound can be filled uniformly (without unevenness) throughout the microporous membrane. In addition, the proton conductivity of the electrolyte membrane impregnated with the electrolyte compound is improved. Therefore, it is preferable. From such a viewpoint, the film thickness of the composite membrane is preferably 15 μm or less, more preferably 12 μm or less, particularly preferably 10 μm or less, and further preferably 9 μm or less.
[0068] Polyolefin microporous membranes are usually white and opaque due to light scattering caused by the presence of pores. However, by substantially filling the pores with an electrolyte compound solution, the light scattering is reduced, and the resulting electrolyte membrane is substantially transparent as a whole in combination with its relatively thin film thickness.
[0069] (Contact angle)
[0070] Based on the viewpoint of the contact angle of the solvent at the membrane surface, polyolefin microporous membranes capable of impregnating solvents with a surface free energy of 28 mJ / m 2 or more can be specified. That is, when the polyolefin microporous membrane of the present invention is placed on a horizontal plane in a state where no hydrophilic treatment has been performed at all and a mixed liquid of ethanol and water (volume ratio 1 / 2; 33% ethanol aqueous solution) is dropped onto its surface, the contact angle between the liquid droplet and the surface 1 second after the drop is preferably 0 to 90 degrees. When the contact angle after 1 second is 90 degrees or less, there is a synergistic effect with the porous structure having the above-mentioned porosity and average pore diameter, and thus the electrolyte solution easily penetrates into the microporous membrane. From this viewpoint, the contact angle after 1 second is more preferably 88 degrees or less, and further preferably 85 degrees or less.
[0071] In addition, for the polyolefin microporous membrane of the present invention, the contact angle between the liquid droplet and the surface 10 minutes after the above-mentioned drop is preferably 0 to 70 degrees. When the contact angle after 10 minutes is 70 degrees or less, it is preferable in terms of the electrolyte solution more easily penetrating into the microporous membrane and enabling the electrolyte compound to be sufficiently filled in the microporous membrane. From this viewpoint, the contact angle after 10 minutes is more preferably 65 degrees or less, and further preferably 60 degrees or less. Here, the contact angle can be measured by the measurement method described in the following examples.
[0072] It should be noted that when the above-mentioned ethanol aqueous solution is dropped onto the polyolefin microporous membrane of the present invention, the liquid droplet penetrates into the microporous membrane in a manner that the liquid droplet does not spread radially outward but has the same diameter or shrinks radially inward.
[0073] (Rate of change of contact angle)
[0074] The polyolefin microporous membrane of the present invention can be defined from the perspective of the change over time of the contact angle described above. That is, for the polyolefin microporous membrane of the present invention, preferably, when a mixed liquid of ethanol and water (volume ratio 1 / 2) is dropped onto its surface in a state where no hydrophilic treatment has been performed, the contact angle θ1 between the liquid droplet and the surface 1 second after dropping is 0 to 90 degrees, and the contact angle θ2 between the liquid droplet and the surface 10 minutes after dropping is 0 to 70 degrees. The change rate of the contact angle ((θ1 - θ2) / θ1 × 100) is 10 to 50%. When the change rate of the contact angle is 10% or more, from the perspective of practical production efficiency, the penetration rate of the electrolyte solution into the polyolefin microporous membrane is sufficient. From this perspective, the change rate of the contact angle is particularly preferably 15% or more, and further preferably 17% or more. On the other hand, from the perspective of sufficiently maintaining the mechanical strength of the polyolefin microporous membrane, the change rate of the contact angle is preferably 45% or less, and more preferably 41% or less.
[0075] In the present invention, it is necessary to adjust the average pore diameter and porosity of the above polyolefin microporous membrane (optionally together with the contact angle) to an appropriate range. As a method for controlling these physical properties, there is no particular limitation, and examples thereof include adjusting the average molecular weight of the polyethylene resin, the mixing ratio when using a plurality of polyethylene resins in combination, the concentration of the polyethylene resin in the raw material, the mixing ratio when using a plurality of solvents in the raw material, the draw ratio, the heat treatment (heat setting) temperature after drawing, the immersion time in the extraction solvent, and other manufacturing conditions. In particular, it can be achieved better by the following operations: as described later, the mass ratio of high molecular weight polyethylene in all polyethylene compositions is 20 to 80% by mass; the raw material uses a polyethylene composition containing 5% by mass or more of high molecular weight polyethylene having a weight average molecular weight of 900,000 or more; as the solvent for the polyolefin solution, a solvent obtained by mixing a volatile solvent and a non-volatile solvent is used (the content of the non-volatile solvent in all solvents is 80 to 98%); the overall draw ratio is 45 to 100 times; or the heat setting temperature is 120 to 135°C.
[0076] (Gurley value)
[0077] The Gurley value of the polyolefin microporous membrane of the present invention measured according to JIS P8117 is preferably 90 seconds / 100 cc or less, more preferably 85 seconds / 100 cc or less, and further preferably 75 seconds / 100 cc or less. When the Gurley value is 90 seconds / 100 cc or less, it is preferable in terms of the easy penetration of the electrolyte compound solution into the microporous membrane and the acceleration of the impregnation rate.
[0078] (Tensile fracture strength)
[0079] For the polyolefin microporous membrane of the present invention, the tensile breaking strength (converted to the value per unit cross-sectional area of the polyolefin solid component) in at least one of the length direction (MD) and the width direction (TD) is preferably 50 MPa or more, and more preferably 60 MPa or more. When the strength of the polyolefin microporous membrane is 50 MPa or more, it is preferable in terms of the mechanical strength of the composite membrane being improved and the operability of the step of impregnating the polyolefin microporous membrane with an electrolyte compound solution being improved.
[0080] (Polyolefin)
[0081] The polyolefin microporous membrane of the present invention is a microporous membrane composed of a polyolefin. Here, the microporous membrane refers to a membrane having a plurality of micropores inside, presenting a structure formed by connecting these micropores, and through which gas or liquid can pass from one surface to the other surface. In the polyolefin microporous membrane, the polyolefin preferably contains 90% by mass or more, more preferably 95% by mass or more, and additives such as organic or inorganic fillers and surfactants may be contained as a balance within a range not affecting the effects of the present invention.
[0082] Examples of the polyolefin include homopolymers or copolymers such as polyethylene, polypropylene, polybutene, and polymethylpentene, or a mixture of one or more of the above. Among them, polyethylene is preferred. As the polyethylene, low molecular weight polyethylene, a mixture of low molecular weight polyethylene and high molecular weight polyethylene, etc. are preferred. In addition, components other than polyethylene may be used in combination. Examples of components other than polyethylene include polypropylene, polybutene, polymethylpentene, and a copolymer formed by polypropylene and polyethylene. In addition, as the polyolefin, a plurality of polyolefins having insufficient compatibility with each other, different degrees of polymerization, and different degrees of branching (in other words, a plurality of polyolefins having different crystallinity, stretchability, and molecular orientation) may be used in combination.
[0083] As the polyolefin used in the present invention, a polyethylene composition containing 5% by mass or more of high molecular weight polyethylene having a weight average molecular weight of 900,000 or more is preferably used, a composition containing 7% by mass or more of high molecular weight polyethylene is more preferably used, and a composition containing 15 to 90% by mass of high molecular weight polyethylene is particularly preferably used. In addition, by appropriately blending two or more kinds of polyethylenes, it has the effect of forming a network structure along with fibrillation during stretching and increasing the porosity generation rate. The weight average molecular weight after blending two or more kinds of polyethylenes is preferably 500,000 to 4,500,000, more preferably 500,000 to 4,000,000. In particular, a polyethylene composition obtained by mixing the above-mentioned high molecular weight polyethylene having a weight average molecular weight of 900,000 or more and low molecular weight polyethylene having a weight average molecular weight of 200,000 to 800,000 is preferably used. In this case, the proportion of the high molecular weight polyethylene in the polyethylene composition is particularly preferably 20 to 80% by mass. The density of the low molecular weight polyethylene is preferably 0.92 to 0.96 g / cm 3 . As the upper limit value of the weight average molecular weight of the high molecular weight polyethylene, it is preferably 6,000,000 or less, particularly preferably 5,000,000 or less. As the lower limit value of the weight average molecular weight of the high molecular weight polyethylene, it is preferably 1,000,000 or more, more preferably 2,000,000 or more, particularly preferably 3,000,000 or more.
[0084] It should be noted that a sample of the polyolefin microporous membrane is heated and dissolved in orthodichlorobenzene, and the weight average molecular weight is measured by GPC (Alliance GPC 2000 type manufactured by Waters Corporation, chromatographic column; GMH6-HT and GMH6-HTL) under the conditions of a column temperature of 135 °C and a flow rate of 1.0 mL / minute. For the molecular weight calibration, monodisperse polystyrene (manufactured by TOSOH Corporation) can be used.
[0085] (Method for manufacturing a polyolefin microporous membrane)
[0086] The polyolefin microporous membrane of the present invention can be preferably manufactured by the following method. That is, it can be preferably manufactured by successively performing the following steps:
[0087] Step (I), preparing a solution containing a polyolefin composition and a solvent and containing at least a volatile solvent having a boiling point lower than 210 °C at atmospheric pressure;
[0088] Step (II), melt-kneading the solution, extruding the obtained melt-kneaded product from a die, and cooling and solidifying to obtain a gel-like molded product;
[0089] Step (III), stretching the gel-like molded product in at least one direction; and
[0090] Step (IV), extracting the solvent from the inside of the stretched intermediate molded product and washing.
[0091] In step (I), a solution containing a polyolefin composition and a solvent is prepared, and a solution containing at least a volatile solvent having a boiling point below 210 °C at atmospheric pressure is prepared. Here, the solution is preferably a thermoreversible sol-gel solution, that is, a thermoreversible sol-gel solution is prepared by heating and dissolving the polyolefin in the solvent to solubilize it. As the volatile solvent having a boiling point below 210 °C at atmospheric pressure in step (I), any liquid solvent that can sufficiently swell the polyolefin or dissolve it can be used without particular limitation, and liquid solvents such as tetralin, ethylene glycol, decalin, toluene, xylene, diethyltriamine, ethylenediamine, dimethyl sulfoxide, and hexane can be preferably selected. These solvents can be used alone or in combination of two or more. Among them, decalin and xylene are preferred.
[0092] In addition, from the aspect of easily adjusting the average pore diameter and porosity to the range of the present invention, in the preparation of this solution, in addition to the above-mentioned volatile solvent having a boiling point below 210 °C at atmospheric pressure, it is preferred to contain a non-volatile solvent having a boiling point of 210 °C or higher, such as liquid paraffin, paraffin oil, mineral oil, and castor oil. In this case, the content of the non-volatile solvent in all the solvents is preferably 80 to 98% by mass.
[0093] In the solution of step (I), from the viewpoint of controlling the filling rate of the electrolyte compound in the polyolefin microporous membrane, the concentration of the polyolefin composition is preferably 10 to 35% by mass, more preferably 15 to 30% by mass.
[0094] In step (II), the solution prepared in step (I) is melt-kneaded, and the obtained melt-kneaded product is extruded from a mold and cooled and solidified to obtain a gel-like molded product. Preferably, an extrudate is obtained by extruding from the mold in the temperature range from the melting point of the polyolefin composition to the melting point + 65 °C, and then the extrudate is cooled to obtain a gel-like molded product.
[0095] As the molded product, it is preferably shaped into a sheet. Cooling can be quenching in an aqueous solution or an organic solvent, or casting onto a cooled metal roll. Usually, the method of quenching in a volatile solvent used in water or a sol-gel solution is used. The cooling temperature is preferably 10 to 40 °C. It should be noted that preferably, while setting a water flow on the surface of the water bath so that the mixed solvent released from the gelled sheet and floating on the water surface in the water bath does not attach to the sheet again, a gel-like sheet is produced.
[0096] In step (II), one or more pre-heatings can also be carried out after the cooling of the gel-like molded product as needed to remove a part of the volatile solvent from the sheet. In this case, the pre-heating temperature is preferably 50 to 100 °C.
[0097] Step (III) is a step of stretching the gel-like formed article in at least one direction. Here, the stretching in step (III) is preferably biaxial stretching, and any one of the sequential biaxial stretching methods of separately performing longitudinal stretching and transverse stretching, and the simultaneous biaxial stretching method of simultaneously performing longitudinal stretching and transverse stretching can be preferably used. In addition, a method of stretching transversely after stretching longitudinally multiple times, a method of stretching transversely multiple times after stretching longitudinally, and a method of stretching longitudinally and / or transversely one or more times further after sequential biaxial stretching are also preferred.
[0098] From the viewpoint of controlling the permeability of the ethanol and water mixture (volume ratio 1 / 2) to the polyolefin microporous membrane, the area stretching ratio (the product of the longitudinal stretching ratio and the transverse stretching ratio) in step (III) is preferably 45 to 100 times, more preferably 50 to 91 times. The stretching temperature is preferably 90 to 110 °C.
[0099] In addition, a heat setting treatment can be performed as needed after the stretching step of (III). From the viewpoint of controlling the filling rate of the resin compound to the polyolefin microporous membrane, the heat setting temperature in this case is preferably 120 to 135 °C.
[0100] Step (IV) is a step of extracting the solvent from the inside of the stretched intermediate formed article and washing it. Here, for step (IV), in order to extract the solvent from the inside of the stretched intermediate formed article (stretched film), it is preferred to wash with halogenated hydrocarbons such as dichloromethane and hydrocarbon solvents such as hexane. When washing by immersing in a tank in which the solvent is accumulated, when it takes 20 to 180 seconds, a polyolefin microporous membrane with a small eluted portion of the residual solvent can be obtained, so it is preferred. In addition, in order to further improve the washing effect, it is preferred to divide the tank into several sections, inject the washing solvent from the downstream side of the conveying process of the polyolefin microporous membrane, circulate the washing solvent toward the upstream side of the process conveyance, and make the purity of the washing solvent in the downstream tank higher than that in the upstream layer. In addition, depending on the performance required for the polyolefin microporous membrane, heat setting can be performed by annealing treatment. It should be noted that from the viewpoint of transportability in the process, etc., the annealing treatment is preferably carried out at 60 to 130 °C, more preferably 70 to 125 °C.
[0101] The polyolefin microporous membrane of the present invention is manufactured through the above steps, and is characterized in that even without performing a hydrophilization treatment accompanied by chemical treatment (for example, coating with a surfactant, graft polymerization using a hydrophilic functional group, wetting treatment with a liquid having a low surface free energy, etc.) or physical treatment (for example, plasma treatment, corona treatment, etc.), it is still possible to impregnate a solution with a high surface free energy well.
[0102] By not performing the above-described chemical treatment, it is possible to prevent the inclusion of unnecessary substances, and the manufacturing cost can also be reduced accordingly. In addition, by not performing the physical treatment, it is possible to prevent the deterioration of the resin and the reduction of the mechanical strength.
[0103] (Electrolyte)
[0104] The electrolyte membrane of the present invention contains a dispersion composition of a perfluorosulfonic acid polymer having an EW of 250 to 850. As such a perfluorosulfonic acid polymer, a fluorine-containing ion exchange resin having an EW of 250 to 850 and containing repeating units represented by the following formulas (1) and (2) is preferably used.
[0105] [Chemical formula 1]
[0106] -(CFZCF3)- (1)
[0107] [Chemical formula 2]
[0108]
[0109] In the above formula, Z is H, Cl, F, or a perfluoroalkyl group having 1 to 3 carbon atoms, m is an integer of 0 to 12, and n is an integer of 0 to 2.
[0110] A suitable fluorine-containing ion exchange resin can be obtained by hydrolyzing a copolymer of a fluorinated olefin represented by the following formula (3) and a fluoroethylene compound represented by the following formula (4).
[0111] [Chemical formula 3]
[0112] CF2=CFZ (3)
[0113] (In the formula, Z is H, Cl, F, or a perfluoroalkyl group having 1 to 3 carbon atoms.)
[0114] [Chemical formula 4]
[0115]
[0116] (In the formula, m is an integer of 0 to 12, n is an integer of 0 to 2, and W is a functional group that can be converted to SO3H by hydrolysis.)
[0117] Here, the functional group W that can be converted to SO3H by hydrolysis is not particularly limited, and examples thereof include SO2F, SO2Cl, and SO2Br.
[0118] A fluorine-containing ion exchange resin precursor containing a copolymer of the above formulas (3) and (4) in which W = SO2F and Z = F is preferably used.
[0119] The above-mentioned fluorine-containing ion exchange resin precursor can be synthesized by known means. For example, the following methods can be cited: a method of using a polymerization solvent such as a fluorinated hydrocarbon, filling and dissolving the fluoroolefin represented by the above formula (3) (hereinafter sometimes simply referred to as "fluoroolefin") and the vinyl fluoride compound represented by the above formula (4) (hereinafter sometimes simply referred to as "vinyl fluoride compound"), and polymerizing by reacting them (solution polymerization); a method of polymerizing without using a solvent such as a fluorinated hydrocarbon and using the vinyl fluoride compound itself as a polymerization solvent (bulk polymerization); a method of using an aqueous solution of a surfactant as a medium, filling the fluoroolefin and the vinyl fluoride compound, and polymerizing by reacting them (emulsion polymerization); a method of filling the fluoroolefin and the vinyl fluoride compound into an aqueous solution of a surfactant and a co-emulsifier such as an alcohol, emulsifying them, and polymerizing by reacting them (mini-emulsion polymerization, microemulsion polymerization); a method of filling and suspending the fluoroolefin and the vinyl fluoride compound in an aqueous solution of a suspension stabilizer and polymerizing by reacting them (suspension polymerization), etc. As the fluorine-containing ion exchange resin precursor, a fluorine-containing ion exchange resin precursor produced by any polymerization method can be used.
[0120] As the fluorinated hydrocarbon used in the polymerization solvent for the above solution polymerization, a compound group collectively referred to as "Freon" such as trichlorotrifluoroethane and 1,1,1,2,3,4,4,5,5,5-decafluoropentane can be preferably used.
[0121] As an index of the degree of polymerization of the fluorine-containing ion exchange resin, the melt flow rate measured at a temperature of 270 °C, an orifice inner diameter of 2.09 mm, an orifice length of 8 mm, and a load of 2.16 kg in the fluorine-containing ion exchange resin precursor is preferably used. The melt flow rate of the fluorine-containing ion exchange resin precursor is preferably 0.01 g / 10 minutes or more, more preferably 0.1 g / 10 minutes or more, and further preferably 0.3 g / 10 minutes or more. In addition, the melt flow rate of the fluorine-containing ion exchange resin precursor is preferably 100 g / 10 minutes or less, more preferably 50 g / 10 minutes or less, and further preferably 10 g / 10 minutes or less. By making the melt flow rate of the fluorine-containing ion exchange resin precursor 0.01 g / 10 minutes or more, a dispersion composition of the fluorine-containing ion exchange resin can be easily obtained. In addition, since the viscosity of the obtained dispersion composition is reduced, there is a tendency that the operations in producing an electrolyte membrane or producing an electrode become easier. On the other hand, by making the melt flow rate 100 g / 10 minutes or less, there is a tendency that the strength of the electrolyte membrane produced using this dispersion composition increases. In addition, since the water absorption of the resin can be suppressed, when used as a binder raw material for a gas diffusion electrode, there is a tendency to suppress overflow during the operation of a fuel cell and to obtain good output under a wide range of power generation conditions.
[0122] The fluorine-containing ion exchange resin precursor can be extrusion-molded using an extruder, a nozzle, a mold, etc. There are no particular limitations on the molding method or the shape of the molded body. In order to accelerate the treatment in the subsequent hydrolysis treatment and acid treatment, the molded body is preferably in the form of particles of 0.5 cm 3 or less, and may also be a powder or a thin sheet of resin obtained after polymerization.
[0123] The fluorine-containing ion exchange resin can be produced by hydrolysis treatment, for example, by immersing the above-mentioned fluorine-containing ion exchange resin precursor in an alkaline reaction solution.
[0124] There are no particular limitations on the alkaline reaction solution used in the hydrolysis treatment. An aqueous solution of hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide and potassium hydroxide is preferred. The content of the hydroxides of alkali metals or alkaline earth metals in the aqueous solution is not particularly limited, and is preferably 10 to 30% by mass or less.
[0125] The above-mentioned alkaline reaction solution preferably contains swelling organic solvents such as alcohols such as methanol and ethanol, ketones such as acetone, bipolar solvents such as dimethyl sulfoxide (hereinafter referred to as "DMSO"), N,N-dimethylacetamide (hereinafter referred to as "DMAC"), and N,N-dimethylformamide (hereinafter referred to as "DMF"). The content rate of the above-mentioned organic solvent is preferably 1 to 30% by mass or less in the mixed solvent of the alkaline reaction solution.
[0126] The hydrolysis temperature of the hydrolysis treatment varies depending on the type of solvent used in the hydrolysis treatment, the solvent composition, etc. The higher the hydrolysis temperature, the shorter the treatment time can be. From the aspect of facilitating the treatment of the fluorine-containing ion exchange resin precursor, it is preferably 20 to 160 °C.
[0127] As the reaction time of the hydrolysis treatment, it is sufficient that the functional group W in the above-mentioned fluorine-containing ion exchange resin precursor reacts for a time sufficient to be completely converted to SO3K or SO3Na by hydrolysis, and there are no particular limitations. The reaction time is preferably 0.5 to 48 hours.
[0128] After the fluorine-containing ion exchange resin precursor is hydrolyzed in the alkaline reaction solution, it is washed with water or the like as needed, and then acid treatment is carried out, thereby producing a fluorine-containing ion exchange resin.
[0129] The acid used in the acid treatment may be inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid, or organic acids such as oxalic acid, acetic acid, formic acid, and trifluoroacetic acid, and there are no particular limitations. In addition, the concentration of the acid used in the acid treatment is also not particularly limited. The fluorine-containing ion exchange resin precursor is protonated by this acid treatment to become an SO3H form. Then, it is washed with water or the like as needed.
[0130] The EW of the fluorine-containing ion exchange resin is 250 or more, preferably 350 or more, more preferably 450 or more, and further preferably 500 or more. Additionally, as the upper limit, it is 850, preferably 750 or less, more preferably 650 or less, and further preferably 600 or less. By making the EW 850 or less, an electrolyte membrane with excellent power generation performance can be obtained. Additionally, by making it 250 or more, an electrolyte membrane with excellent mechanical strength can be obtained. The EW of the fluorine-containing ion exchange resin can be measured according to the method described in the examples below.
[0131] (Dispersion composition of fluorine-containing ion exchange resin)
[0132] The dispersion composition of the fluorine-containing ion exchange resin contains the above-mentioned fluorine-containing ion exchange resin and a solvent with a surface free energy of 28 mJ / m 2 or more. Here, the content of the fluorine-containing ion exchange resin in the dispersion composition is preferably 15 to 45% by mass, more preferably 17 to 43% by mass, and further preferably 20 to 40% by mass. When the content of the fluorine-containing ion exchange resin is 15% by mass or more, there is a tendency for the amount of solvent to be removed when making an electrolyte membrane and an electrode using the dispersion composition to decrease, so it is preferred. On the other hand, when it is 45% by mass or less, the viscosity of the obtained dispersion composition is stable over time, and there is a tendency to prevent abnormal viscosity increase and partial gelation during transportation and storage, so it is preferred.
[0133] The dispersion composition of the fluorine-containing ion exchange resin can be manufactured as follows: Mix the above-mentioned fluorine-containing ion exchange resin in a solvent with a surface free energy of 28 mJ / m 2 or more at 1% by mass or more and less than 15% by mass. After subjecting the obtained aqueous composition to a dispersion treatment, the aqueous composition is concentrated so that the concentration of the fluorine-containing ion exchange resin is 15% by mass or more and 45% by mass or less.
[0134] As the solvent with a surface free energy of 28 mJ / m 2 or more, the above-mentioned mixed solvent of an organic solvent and water can be used. Among them, a mixed solvent containing water and alcohols is preferably used. As the alcohols, considering that the boiling points of the alcohols are low-boiling points, alcohols with 1 to 3 carbon atoms are preferred. These alcohols can be used singly or in combination of two or more. Specifically, methanol, ethanol, 1-propanol, 2-propanol, etc. can be mentioned, and methanol and ethanol are preferred. Additionally, the alcohol concentration in the mixed solvent containing water and alcohols is preferably 49.9% by mass or less. By making the alcohol concentration 49.9% by mass or less, the viscosity of the dispersion composition can be reduced. Therefore, the fluorine-containing ion exchange resin can be contained at a high concentration of 15% to 45%.
[0135] In the above-mentioned mixed solvent, glycols such as ethylene glycol, 1,2-propanediol, and 1,3-propanediol, bipolar organic solvents such as DMSO, DMAC, and DMF, fluorinated alcohols, and fluorinated ethers can also be mixed within the range that does not impair the desired effects, and their concentration is preferably 5% by mass or less in the entire mixed solvent.
[0136] (Method for manufacturing an electrolyte membrane)
[0137] The electrolyte membrane of the present invention can be manufactured through the following steps: a step of impregnating the following solution into a polyolefin microporous membrane, wherein the average pore diameter of the polyolefin microporous membrane is 1 to 1000 nm, the porosity is 50 to 90%, and it can impregnate a solvent with a surface free energy of 28 mJ / m 2 or more, and the solution is obtained by dissolving an electrolyte of a perfluorosulfonic acid polymer having an EW of 250 to 850 in the solvent; a step of drying the polyolefin microporous membrane after the impregnation step to remove the solvent; and a step of annealing the polyolefin microporous membrane after the removal step. For the polyolefin microporous membrane of the present invention, without performing a forced filling treatment based on pressurization or depressurization, a solvent with a surface free energy of 28 mJ / m 2 or more can spontaneously penetrate into the pores just by contacting the microporous membrane. Therefore, for the impregnation step, for example, in an atmospheric atmosphere, the electrolyte solution is spread on a glass substrate, and the polyolefin microporous membrane is placed on the electrolyte solution and only contacted. The solvent removal step after the impregnation step can be performed only by natural drying, that is, the polyolefin microporous membrane containing the electrolyte solution is simply placed in an atmospheric atmosphere. In addition, in order to achieve uniform distribution of the electrolyte polymer inside the electrolyte membrane, an additional electrolyte solution can also be used from above the polyolefin microporous membrane after the natural drying, that is, from the side opposite to the glass substrate, and the impregnation-drying steps can be repeated. By annealing the electrolyte membrane after the drying step, the complexation between the electrolyte polymers can be promoted, thereby improving the physical strength of the electrolyte membrane. As the conditions for the annealing treatment, considering maintaining the porous structure of the polyolefin microporous membrane and approaching the glass transition temperature of the electrolyte polymer, it is preferably treated at about 100°C for about 10 to 20 hours.
[0138] (Membrane electrode assembly: MEA)
[0139] When the electrolyte membrane of the present invention is applied to a polymer electrolyte fuel cell, gas diffusion electrodes including catalyst layers are provided on both surfaces of the electrolyte membrane, with one surface serving as the anode and the other surface serving as the cathode. The thickness of the catalyst layer of the gas diffusion electrode in the membrane electrode assembly is not particularly limited. From the viewpoint of facilitating the diffusion of gas in the catalyst layer and improving the cell characteristics, the thickness of the catalyst layer is preferably 20 μm or less, and more preferably uniform. By using the above-described dispersion composition containing a fluorine-containing ion exchange resin, a catalyst layer with a thickness of 20 μm or less can be formed with a uniform thickness. When the thickness of the catalyst layer is made thin, the amount of catalyst present per unit area decreases, and there is a possibility of a decrease in reaction activity. However, in this case, if a supported catalyst in which platinum or a platinum alloy is supported at a high loading rate is used as the catalyst, even if it is thin, the amount of catalyst will not be insufficient, and thus the reaction activity of the electrode can be maintained at a high level. From the above viewpoints, the thickness of the catalyst layer is more preferably 1 to 15 μm.
[0140] The gas diffusion electrode can be manufactured, for example, by coating the surface of a commercially available gas diffusion electrode with the above-described dispersion composition containing a fluorine-containing ion exchange resin and then drying and immobilizing it at 140 °C in an air atmosphere. Alternatively, a coating liquid containing the dispersion composition containing a fluorine-containing ion exchange resin and catalyst powder in which catalyst metal particles are supported on a carbon carrier is prepared, and the coating liquid is coated on a substrate, whereby a catalyst layer of at least one of the anode and the cathode can be formed. The catalyst layer obtained by this method has few defects such as cracking and excellent smoothness. Since the catalyst layer is formed by removing the solvent (dispersion medium) after coating the coating liquid, the strength of the ion exchange polymer that functions not only as an electrolyte but also as a binder for the catalyst is increased, thereby preventing cracking of the catalyst layer.
[0141] Solvents can be further added to the coating solution. As the added solvents, alcohols, fluorinated solvents or water are preferred. Alcohols are preferably selected, and alcohols having 1 to 4 carbon atoms in the main chain are preferred. Examples thereof include methanol, ethanol, n-propanol, isopropanol, tert-butanol, etc. In addition, when water is mixed with the alcohol, the solubility of the fluorine ion exchange resin can be improved. As the fluorinated solvent, for example, hydrofluorocarbons such as 2H-perfluoropropane, 1H,4H-perfluorobutane, 2H,3H-perfluoropentane, 3H,4H-perfluoro(2-methylpentane), 2H,5H-perfluorohexane, 3H-perfluoro(2-methylpentane); fluorocarbons such as perfluoro(1,2-dimethylcyclobutane), perfluorooctane, perfluoroheptane, perfluorohexane; hydrochlorofluorocarbons such as 1,1-dichloro-1-fluoroethane, 1,1,1-trifluoro-2,2-dichloroethane, 3,3-dichloro-1,1,1,2,2-pentafluoropropane, 1,3-dichloro-1,1,2,2,3-pentafluoropropane; fluorinated ethers such as 1H,4H,4H-perfluoro(3-oxapentane), 3-methoxy-1,1,1,2,3,3-hexafluoropropane; fluorinated alcohols such as 2,2,2-trifluoroethanol, 2,2,3,3,3-pentafluoro-1-propanol, 1,1,1,3,3,3-hexafluoro-2-propanol, etc.
[0142] The solid component concentration of the coating solution can be appropriately selected according to the thickness of the target catalyst layer and is not particularly limited. In order to form a uniform coating layer, it is preferably 1 to 50% by mass, more preferably 5 to 35% by mass, based on the mass ratio with respect to the total mass. The substrate coated with the above coating solution can be an ion exchange membrane or a gas diffusion layer disposed outside the catalyst layer and acting as a current collector. In addition, it can also be a separately prepared substrate that is not a constituent material of the membrane electrode assembly. In this case, the substrate can be peeled off after the catalyst layer is bonded to the membrane. As the separately prepared substrate, there is no particular limitation, and a film made of a material selected from polyethylene terephthalate, polyethylene naphthalate, polypropylene, polyethylene, polymethylpentene, polyimide, polyphenylene sulfide, polytetrafluoroethylene, etc. can be used.
[0143] As a method for manufacturing the membrane electrode assembly, for example, (1) a method of directly coating the above coating solution on the electrolyte membrane, then drying to remove the dispersion medium contained in the coating solution to form a catalyst layer, and sandwiching the gas diffusion layer from both sides; (2) a method of coating the above coating solution on a substrate such as carbon paper, carbon cloth or carbon felt used as the gas diffusion layer, drying to form a catalyst layer, and then bonding it to the solid polymer electrolyte membrane by a method such as hot pressing; (3) a method of coating the above coating solution on a membrane (substrate) that exhibits sufficient stability with respect to the solvent contained in the coating solution, drying it, hot pressing it on the solid polymer electrolyte membrane, and then peeling off the substrate membrane and sandwiching the gas diffusion layer; and so on.
[0144] The coating method is not particularly limited. For example, as batch methods, there are bar coating, spin coating, screen printing, etc. As continuous methods, post-metering and pre-metering methods can be cited. The post-metering method is a method of coating an excessive amount of coating liquid and then removing the coating liquid so as to form a specified film thickness. The pre-metering method is a method of coating the amount of coating liquid required to obtain a specified film thickness. As the post-metering method, there are air knife coater method, blade coater method, bar coating method, blade coater method, extrusion coater method, impregnation coater method, comma blade coater method, etc. As the pre-metering method, there are die coater method, reverse roll coater method, transfer roll coater method, gravure printer method, kiss roll coater method, casting coater method, spraying machine method, curtain coater method, sizing calender method, extrusion coater method, etc. In order to form a uniform catalyst layer, screen printing method and die coater method are preferred. Considering production efficiency, the continuous die coater method is more preferred.
[0145] The catalyst contained in the catalyst layer can be the same or different on the anode side and the cathode side. It is preferred to support a metal catalyst containing platinum or a platinum alloy on carbon. The specific surface area of the carbon serving as the carrier is preferably 50 to 1500 m 2 / g. Thus, the metal catalyst can be supported on the carbon carrier with good dispersibility, and the activity of the electrode reaction is excellent and stable for a long time.
[0146] As the metal catalyst, a metal catalyst containing platinum has high activity for the hydrogen oxidation reaction at the anode and the oxygen reduction reaction at the cathode in a polymer electrolyte fuel cell, and is therefore preferred. There are cases where a metal catalyst containing a platinum catalyst can further impart stability and activity as an electrode catalyst, and is therefore also preferred. As the above platinum alloy, it is preferably an alloy formed by one or more metals selected from the group consisting of platinum group metals other than platinum (ruthenium, rhodium, palladium, osmium, iridium), gold, silver, chromium, iron, titanium, manganese, cobalt, nickel, molybdenum, tungsten, aluminum, silicon, zinc, and tin and platinum. In this platinum alloy, an intermetallic compound formed by the metal alloyed with platinum and platinum may also be contained. When a gas containing carbon monoxide is supplied to the anode, when an alloy containing platinum and ruthenium is used, the activity of the catalyst is stable, and is therefore preferred.
[0147] In the membrane electrode assembly for a fuel cell, an oxygen-containing gas is supplied to the cathode, and a hydrogen-containing gas is supplied to the anode. Specifically, for example, a separator having a groove serving as a gas flow path is disposed outside the electrode of the membrane electrode assembly, and a gas is circulated in the gas flow path to supply a gas serving as fuel to the membrane electrode assembly to generate electricity. In addition, it can also be used as a membrane electrode assembly for a direct methanol fuel cell (which supplies methanol as a fuel gas).
[0148] Embodiment
[0149] Hereinafter, this embodiment will be described in more detail by way of examples, but this embodiment is not limited to these examples. It should be noted that the evaluation methods and measurement methods used in this embodiment are as follows.
[0150] (Weight-average molecular weight of polyolefin)
[0151] A sample of the polyolefin microporous membrane is heated and dissolved in orthodichlorobenzene, and measured by GPC (Alliance GPC 2000 type manufactured by Waters Corporation, chromatographic columns; GMH6-HT and GMH6-HTL) under the conditions of a column temperature of 135 °C and a flow rate of 1.0 mL / minute, whereby the weight-average molecular weight is obtained. For the calibration of the molecular weight, monodisperse polystyrene (manufactured by TOSOH Corporation) can be used.
[0152] (Film thickness)
[0153] The film thickness of the sample is obtained by measuring 20 points using a contact-type film thickness gauge (Litematic VL-50A manufactured by Mitsutoyo Corporation) and averaging them. Here, a cylindrical contact terminal with a bottom diameter of 0.5 cm is used as the contact terminal. In the measurement, it is adjusted by applying a load of 0.01 N.
[0154] (Average pore diameter)
[0155] Regarding the average fine pore diameter of the polyolefin microporous membrane, using a Perm-Porometer (model: CFP-1500AEX) from Porous Materia, and using GALWICK (perfluoropolyether; manufactured by Porous Materia, surface tension 15.9 dyne / cm) as the impregnating liquid, based on the semi-dry method specified in ASTM E1294-89, the average flow pore diameter (nm) is calculated. The measurement temperature is 25 °C, and the measurement pressure is 200 kPa to 3500 kPa.
[0156] (Porosity)
[0157] The porosity (ε) of the polyolefin microporous membrane is calculated by the following formula.
[0158] ε (%) = {1 - Ws / (ds·t)} × 100
[0159] Ws: Unit area weight of the polyolefin microporous membrane (g / m 2 )
[0160] ds: True density of the polyolefin (g / cm 3 )
[0161] t: Film thickness of the polyolefin microporous membrane (μm)
[0162] Note that for the weight per unit area of the polyolefin microporous membrane, the sample is cut into 10 cm × 10 cm, its mass is measured, and the weight per unit area is obtained by dividing the mass by the area.
[0163] (Contact angle)
[0164] As the measuring device, a fully automatic contact angle meter DMo-701FE and an Interface Measurement and Analysis System FAMAS manufactured by Kyowa Interface Science Co., Ltd. are used to measure the static contact angle. For the polyolefin microporous membrane in the state without hydrophilic treatment, 4 μL of an ethanol aqueous solution (industrial ethanol (purity 95%) / pure water mixed volume ratio 1 / 2) is dropped onto the specimen, and the contact angle θ1 1 second after dropping and the contact angle θ2 10 minutes after dropping are measured at 24 °C and a relative humidity of 60% under normal pressure in the atmosphere.
[0165] (Gurley value)
[0166] According to JIS P8117, the Gurley value (seconds / 100 cc) of the polyolefin microporous membrane with an area of 642 mm 2 is measured.
[0167] (Tensile fracture strength)
[0168] Using a tensile testing machine (RTE-1210 manufactured by Orientec), a strip-shaped test piece (width 15 mm, length 50 mm) is stretched at a speed of 200 mm / minute, and the tensile strength at the time of rupture of the test piece is obtained.
[0169] (Change rate of contact angle)
[0170] Based on the contact angle θ1 1 second after liquid dropping and the contact angle θ2 10 minutes after liquid dropping obtained from the above measurement of the contact angle, the change rate of the contact angle is calculated using the following formula as an index of the permeation rate. For example, in the case of two samples with the same contact angle θ1 1 second after dropping, the greater the change rate of the contact angle θ2 10 minutes after dropping, the higher the permeation rate.
[0171] Change rate of contact angle = (θ1 - θ2) / θ1 × 100 (%)
[0172] (Permeability of ethanol aqueous solution)
[0173] Prepare an ethanol aqueous solution by mixing industrial ethanol (purity 95%) with various volume ratios relative to pure water. Closely place the sample on a piece of paper with good visual recognition of water absorption. Drop 10 μL of the prepared ethanol aqueous solution onto the sample, and observe whether the dropped liquid penetrates under normal atmospheric pressure, at 24 °C, and a relative humidity of 60%. Visually confirm whether the paper is wetted 1 minute after dropping to determine whether penetration has occurred. It should be noted that when the paper on the back changes color, it is judged as complete penetration (○), and when it does not change color, it is judged that the liquid drop has not reached the back and thus has not penetrated (×). The highest water concentration represents the highest water concentration among the water concentrations of the ethanol aqueous solutions in which the liquid drops penetrate (it should be noted that the water concentration is calculated based on converting the ethanol concentration to a purity of 100%). In addition, the surface free energy of the ethanol aqueous solution at the highest water concentration is also shown in Table 1 below.
[0174] (EW of fluorine-containing ion exchange resin)
[0175] Immerse about 0.02 - 0.10 g of the acid-type fluorine-containing ion exchange resin in 50 mL of a 25 °C saturated NaCl aqueous solution (0.26 g / mL), let it stand for 10 minutes while stirring, and then use Wako Pure Chemical Industries, Ltd. reagent special grade phenolphthalein as an indicator and Wako Pure Chemical Industries, Ltd. reagent special grade 0.01 N sodium hydroxide aqueous solution for neutralization titration. Wash the obtained Na-type ion exchange membrane with pure water, then vacuum dry and weigh it. Let the equivalent of sodium hydroxide required for neutralization be M (mmol), and the mass of the Na-type ion exchange membrane be W (mg), and use the following formula to calculate the equivalent weight EW (g / eq).
[0176] EW = (W / M) - 22
[0177] (Melt flow rate (MFR) of fluorine-containing ion exchange resin precursor)
[0178] Based on JIS K-7210, use a device with an orifice inner diameter of 2.09 mm and a length of 8 mm to measure the melt flow rate (MFR, g / 10 minutes) of the fluorine-containing ion exchange resin precursor at a temperature of 270 °C and a load of 2.16 kg.
[0179] (Concentration of fluorine-containing ion exchange resin in the dispersion composition)
[0180] Precisely weigh the mass of a weighing bottle at room temperature that has been dried, and set it as W0. Load 10 g of the test substance into the measured weighing bottle, precisely weigh it, and set it as W1. Use a vacuum dryer LV-120 manufactured by Espec Corporation to dry the weighing bottle containing the test substance at a temperature of 110 °C and an absolute pressure of 0.01 MPa or less for 3 hours or more, then cool it in a desiccator containing silica gel. After it becomes room temperature, precisely weigh it and set it as W2. Express (W2 - W0) / (W1 - W0) as a percentage, measure it 5 times, and take the average value as the concentration of the fluorine-containing ion exchange resin.
[0181] (Proton Conductivity of the Electrolyte Membrane)
[0182] The proton conductivity of the electrolyte membrane is evaluated by measuring using the four-terminal AC impedance method in the in-plane direction of the membrane surface. Platinum plates are used as electrodes. For each platinum plate, two glass slides are used to sandwich the electrolyte membrane, and both ends of the glass slides are fixed with a clamp. The electrolyte membrane is placed in a constant temperature bath SH-241 (manufactured by Espec Corporation), the temperature is 80 °C, and the relative humidity is changed at intervals of 10% RH from 90% RH to 20% RH. At each humidity, it is stabilized for at least 4 hours, and then the AC impedance method measurement is performed. The AC impedance method measurement uses an impedance analyzer Solartron 1260 (manufactured by Solartron in the UK), and the AC amplitude is set to a value between 10 and 100 mV, and the frequency is scanned from 100,000 Hz to 1 Hz or less.
[0183] (Fuel Cell Evaluation)
[0184] Put 10.84 g of a dispersion composition of a fluorine-containing ion exchange resin EW560, which is the same as the raw material used as the electrolyte membrane described later, 2.0 g of TKK Pt / C (TEC10E50E platinum loading 45.9% manufactured by Tanaka Precious Metals Co., Ltd.) as a catalyst, 8.67 g of RO water, 8.67 g of 1-propanol, 8.67 g of 2-propanol, and zirconia beads 200 g into a zirconia container together, and use a planetary ball mill (manufactured by Fritsch in Germany) to ball mill and mix at a rotation speed of 200 rpm for 1 hour to prepare a coating solution.
[0185] The electrode catalyst layer is prepared by coating the coating solution prepared above on a polytetrafluoroethylene (PTFE) sheet using a coater PI-1210 (Tester Sangyo) and drying it in an air atmosphere. The platinum loading is adjusted to about 0.3 mg / cm 2 or so.
[0186] The MEA is prepared by sandwiching the electrolyte membrane between two pieces cut into 5 cm 2After hot pressing for 1 minute at 135 °C and a pressure of 2.0 kN between the above-mentioned electrode catalyst layers, the PTFE sheet was peeled off to fabricate (decal method).
[0187] Both sides of the above MEA were clamped with a gas diffusion layer (SIGRACET GDL 24BC manufactured by SGL GROUP), and assembled into a single cell (catalyst layer area: 5 cm 2 ) manufactured by Electro Chem together with gaskets. The cell temperature was set at 80 °C, and the relative humidity of the gases flowing through both electrodes was controlled by the water bubbling method. Two kinds of electrochemical property measurements were carried out. One is the current interrupt method. Hydrogen and oxygen were allowed to flow through the anode side and the cathode side at flow rates of 100 mL / min and 500 mL / min, respectively. The relative humidity of both electrodes was simultaneously changed to 60% RH, 30% RH, 20% RH, and 10% RH. Using an electrochemical measurement system HZ-3000 (Hokuto Denko Corporation), with 1 A / cm 2 As the initial state, current was allowed to flow through the cell for 1 minute, and the voltage change when the current was instantaneously cut off was measured, from which the ohmic resistance was calculated. The second is the I-V characteristic test. Hydrogen as fuel and oxygen or air as oxidant were allowed to flow through the anode side and the cathode side at flow rates of 100 mL / min and 500 mL / min, respectively. The relative humidity of both electrodes was simultaneously changed to 30% RH, 20% RH, and 10% RH. The cell voltage was measured when the current was scanned from 0 to 10 A (driven) using a battery charge-discharge device HJ1010SM8A (Hokuto Denko Corporation).
[0188] (Fabrication of polyolefin microporous membrane)
[0189] (Production Example 1)
[0190] A polyethylene composition was used, which was mixed with 12 parts by mass of high molecular weight polyethylene (PE1) having a weight average molecular weight of 4.6 million and 3 parts by mass of low molecular weight polyethylene (PE2) having a weight average molecular weight of 0.56 million. A polyethylene solution was prepared by mixing 72 parts by mass of pre-prepared liquid paraffin and 13 parts by mass of decalin (decahydronaphthalene) as a mixed solvent so that the concentration of the total amount of the polyethylene resin became 15% by mass.
[0191] The polyethylene solution is extruded from a die into a sheet at a temperature of 160°C, and then the extrudate is cooled in a water bath at 25°C. While setting a water flow on the surface layer of the water bath so that the mixed solvent released from the gelled sheet and floating on the water surface in the water bath does not attach to the sheet again, a gel-like sheet (base film) is produced. The base film is dried at 55°C for 10 minutes and further dried at 95°C for 10 minutes to remove decalin from the base film. Then, the base film is stretched in the length direction at a temperature of 100°C at a magnification of 5.5 times, and then stretched in the width direction at a temperature of 110°C at a magnification of 13 times, and then immediately heat-treated (heat-fixed) at 135°C.
[0192] Next, while continuously immersing the polyethylene microporous membrane in a dichloromethane bath divided into two tanks for 30 seconds each, liquid paraffin is extracted. It should be noted that when the side where immersion starts is the first tank and the side where immersion ends is the second tank, the purity of the washing solvent is (low) the first tank < the second tank (high). Then, it is dried at 45°C to remove dichloromethane, and annealing treatment is carried out while conveying it on a roller heated to 120°C, thereby obtaining a polyolefin microporous membrane.
[0193] The obtained polyolefin microporous membrane has excellent permeability in an ethanol / water = 1 / 2 (volume ratio) solution and is suitable as a base material for a composite membrane. It should be noted that the physical property values and evaluation results of the polyethylene microporous membrane are shown in Table 1 below.
[0194] (Production Example 2)
[0195] A polyethylene composition mixed with 6 parts by mass of high molecular weight polyethylene (PE1) having a weight average molecular weight of 4.6 million and 24 parts by mass of low molecular weight polyethylene (PE2) having a weight average molecular weight of 560,000 in Production Example 1 was used. A mixed solvent of 6 parts by mass of decalin (decahydronaphthalene) and 64 parts by mass of paraffin prepared in advance was mixed so that the concentration of the total amount of the polyethylene resin became 30% by mass to prepare a polyethylene solution.
[0196] The polyethylene solution is extruded from a die into a sheet at a temperature of 160°C, and then the extrudate is cooled in a water bath at 25°C to produce a gel-like sheet.
[0197] The base film is dried at 55°C for 10 minutes and further dried at 95°C for 10 minutes to remove decalin from the base film. Then, the base film is stretched in the length direction at a temperature of 100°C at a magnification of 5.5 times, and then stretched in the width direction at a temperature of 110°C at a magnification of 13 times, and then immediately heat-treated (heat-fixed) at 125°C. Except for this, a polyolefin microporous membrane is obtained in the same manner as in Production Example 1.
[0198] As shown in Table 1 below, the obtained polyolefin microporous membrane has excellent permeability in an ethanol / water = 1 / 2 solution and is suitable as a base material for a composite membrane.
[0199] (Production Example 3)
[0200] A polyethylene composition was used, which was a mixture of 16 parts by mass of a high molecular weight polyethylene (PE1) with a weight average molecular weight of 4.6 million in Production Example 1 and 4 parts by mass of a low molecular weight polyethylene (PE2) with a weight average molecular weight of 0.56 million. A mixed solvent of 2 parts by mass of decalin (decahydronaphthalene) and 78 parts by mass of paraffin wax prepared in advance was mixed so that the concentration of the total amount of the polyethylene resin became 20% by mass to prepare a polyethylene solution.
[0201] The polyethylene solution was extruded into a sheet from a die at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C to produce a gel-like sheet.
[0202] The base sheet was dried at 55°C for 10 minutes and then further dried at 95°C for 10 minutes to remove decalin from the base sheet. Then, the base sheet was stretched in the length direction at a temperature of 100°C at a magnification of 3.9 times, and then in the width direction at a temperature of 100°C at a magnification of 13 times, and then immediately heat-treated (heat-fixed) at 135°C. Except for this, a polyolefin microporous membrane was obtained in the same manner as in Production Example 1.
[0203] As shown in Table 1 below, the obtained polyolefin microporous membrane has excellent permeability in an ethanol / water = 1 / 2 solution and is suitable as a base material for a composite membrane.
[0204] (Production Example 4)
[0205] A polyethylene composition was used, which was a mixture of 16 parts by mass of a high molecular weight polyethylene (PE1) with a weight average molecular weight of 4.6 million in Production Example 1 and 4 parts by mass of a low molecular weight polyethylene (PE2) with a weight average molecular weight of 0.56 million. A mixed solvent of 2 parts by mass of decalin (decahydronaphthalene) and 78 parts by mass of paraffin wax prepared in advance was mixed so that the concentration of the total amount of the polyethylene resin became 20% by mass to prepare a polyethylene solution.
[0206] The polyethylene solution was extruded into a sheet from a die at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C to produce a gel-like sheet.
[0207] The base sheet was dried at 55°C for 10 minutes and then further dried at 95°C for 10 minutes to remove decalin from the base sheet. Then, the base sheet was stretched in the length direction at a temperature of 100°C at a magnification of 5 times, and then in the width direction at a temperature of 105°C at a magnification of 9 times, and then immediately heat-treated (heat-fixed) at 135°C. Except for this, a polyolefin microporous membrane was obtained in the same manner as in Production Example 1.
[0208] As shown in Table 1 below, the obtained polyolefin microporous membrane has excellent permeability in an ethanol / water = 1 / 2 solution and is suitable as a base material for a composite membrane.
[0209] (Production Example 5)
[0210] A polyethylene solution was prepared in the same manner as in Production Example 1.
[0211] The polyethylene solution was extruded from a die into a sheet at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C to produce a gel-like sheet.
[0212] The base sheet was dried at 55°C for 10 minutes and then at 95°C for 10 minutes to remove decalin from the base sheet. Then, the base sheet was stretched in the length direction at a temperature of 100°C at a magnification of 7 times, and then in the width direction at a temperature of 100°C at a magnification of 13 times, and then immediately heat-treated (heat-fixed) at 135°C. Except for this, a polyolefin microporous membrane was obtained in the same manner as in Production Example 1.
[0213] As shown in Table 1 below, the obtained polyolefin microporous membrane has excellent permeability in an ethanol / water = 1 / 2 solution and is suitable as a base material for a composite membrane.
[0214] (Production Example 6)
[0215] A polyethylene composition in which 6 parts by mass of high molecular weight polyethylene (PE1) having a weight average molecular weight of 4.6 million and 6 parts by mass of low molecular weight polyethylene (PE2) having a weight average molecular weight of 0.56 million in Production Example 1 were mixed was used. A mixed solvent of 30 parts by mass of decalin (decahydronaphthalene) and 58 parts by mass of paraffin wax prepared in advance was mixed so that the concentration of the total amount of the polyethylene resin became 12% by mass to prepare a polyethylene solution.
[0216] The polyethylene solution was extruded from a die into a sheet at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C to produce a gel-like sheet.
[0217] The base sheet was dried at 55°C for 10 minutes and then at 95°C for 10 minutes to remove decalin from the base sheet. Then, the base sheet was stretched in the length direction at a temperature of 110°C at a magnification of 6.5 times, and then in the width direction at a temperature of 115°C at a magnification of 15 times, and then immediately heat-treated (heat-fixed) at 138°C. Except for this, a polyolefin microporous membrane was obtained in the same manner as in Production Example 1.
[0218] As shown in Table 1 below, the obtained polyolefin microporous membrane has excellent permeability in an ethanol / water = 1 / 2 solution and is suitable as a base material for a composite membrane.
[0219] [Table 1]
[0220]
[0221] (Manufacture of fluorine-containing ion exchange resin)
[0222] Using an extruder, at 270 °C, the fluorine-containing ion exchange resin precursor composed of the copolymer (MFR = 3.0) formed by the fluoroolefin (CF2=CF2) with Z = F in the aforementioned formula (3) and the fluoroethylene compound (CF2=CF-O-(CF2)2-SO2F) with m = 2, n = 0, and W = SO2F in the aforementioned formula (4) was extruded from a circular nozzle and then cut to produce cylindrical pellets with a diameter of 2 - 3 mm and a length of 4 - 5 mm. 510 g of the fluorine-containing ion exchange resin precursor pellets were immersed in 3160 g of an aqueous KOH solution (KOH and DMSO were added and adjusted in advance so that the KOH concentration was 15% by mass and the DMSO concentration was 30% by mass) for 6 hours to convert the SO2F groups in the fluorine-containing ion exchange resin precursor into SO3K groups.
[0223] After the above-mentioned treated pellets were immersed in 1N-HCl (2500 mL) at 60 °C for 6 hours, they were washed with ion-exchanged water (conductivity of 0.06 S / cm or less) at 60 °C and dried to obtain the fluorine-containing ion exchange resin with a proton exchange group in which the aforementioned SO3K groups had become SO3H groups (EW = 560 g / eq).
[0224] Next, in an autoclave with a glass inner cylinder and a capacity of 5 L made of SUS304, 120 g of the above-mentioned fluorine-containing ion exchange resin (water content of 28.7% by mass), 485 g of ethanol, and 949 g of ion-exchanged water were charged into the glass inner cylinder, and 70 g of ethanol and 140 g of ion-exchanged water were charged between the inner cylinder and the inner wall of the autoclave. While stirring the liquid in the glass inner cylinder, a dispersion treatment was carried out at 162 °C for 4 hours. While heating, the pressure inside the autoclave was increased, and the maximum pressure was 1.2 MPa. After cooling, it was taken out from the autoclave to obtain a uniform and transparent dispersion composition of the fluorine-containing ion exchange resin. The composition of this dispersion composition was 5.0% by mass of the fluorine-containing ion exchange resin, 30.0% by mass of ethanol, and 65.0% by mass of water.
[0225] Then, 350 g of the above-mentioned dispersion composition was charged into a 500 mL eggplant-shaped flask, and using a rotary evaporator R-200 manufactured by BUCHI, it was rotated at 80 °C at 40 rpm, and at the same time, azeotropic distillation was carried out under a reduced pressure of 0.04 MPa, thereby concentrating until the concentration of the fluorine-containing ion exchange resin became 15% by mass to obtain a dispersion composition. The composition of this dispersion composition was 9.8% by mass of the fluorine-containing ion exchange resin, 8.3% by mass of ethanol, and 81.9% by mass of water.
[0226] (Fabrication of electrolyte membrane for solid polymer fuel cell)
[0227] Impregnate and support perfluorosulfonic acid polymer (EW560) within the pores of the above-mentioned polyethylene microporous membrane to fabricate the electrolyte membrane of a solid polymer fuel cell.
[0228] (1) Study on solvent ratio
[0229] Before impregnation, place the above-mentioned polyethylene microporous membrane (white opaque membrane) on a glass plate, gently drip a water / ethanol mixed solution from above, and confirm the color change of the microporous membrane. The mixed solutions used are A: water / ethanol = 4 / 1 (mass ratio), B: water / ethanol = 3 / 1 (mass ratio), and C: water / ethanol = 2 / 1 (mass ratio). As a result, only the mixed solution C (water / ethanol = 2 / 1 (mass ratio)) changed the color of the microporous membrane to transparent, so it was confirmed that the pores of the microporous membrane were filled with the mixed solution. It should be noted that for the mixed solutions A and B, the color of the microporous membrane remained white opaque without change, and the mixed solution did not penetrate into the pores of the microporous membrane. In the following examples, the mixed solution C (water / ethanol = 2 / 1 (mass ratio)) was used to fabricate the electrolyte membrane.
[0230] [Example 1]
[0231] (Fabrication of electrolyte membrane of solid polymer fuel cell)
[0232] Dissolve the above-mentioned perfluorosulfonic acid polymer in a mixed solution of water / ethanol = 2 / 1 (mass ratio) at a polymer concentration of 3.3% by mass to prepare a polymer solution. Immerse the polyethylene microporous membrane obtained in Production Example 1 in ethanol, perform ultrasonic washing for 1 hour, and then dry it overnight in an air atmosphere. Thinly apply about 0.3 ml of the above polymer solution on a glass dish, gently place the above polyethylene microporous membrane (thickness 6 μm, porosity 66%, size about 10 mm × 30 mm) on it, and dry it overnight in an air atmosphere. Then, further thinly apply about 0.3 ml of the above polymer solution on the polyethylene microporous membrane and dry it overnight in the same way to remove the solvent. Next, anneal the polyolefin microporous membrane impregnated with perfluorosulfonic acid polymer at 100 °C for 13.5 hours, take out the electrolyte membrane from the glass dish, stir it in a 1M nitric acid aqueous solution at 90 °C for 1 hour for proton replacement, and then stir it in RO water at 90 °C for 1 hour for washing. Thus, an electrolyte membrane containing a composite membrane (membrane thickness 11.8 μm) was obtained.
[0233] [Comparative Example 1]
[0234] Except for using perfluorosulfonic acid polymer EW900, operate in the same manner as above to fabricate an electrolyte membrane containing a composite membrane (membrane thickness 16.6 μm).
[0235] [Reference Example 1]
[0236] As a reference example, the electrolyte membrane Nafion NR211 (membrane thickness 25 μm) of Dupont was used.
[0237] (Evaluation of Proton Conductivity)
[0238] The proton conductivity of the electrolyte membrane of the perfluorosulfonic acid polymer filled with EW560 and EW900 was evaluated by measurement using the alternating current impedance method (In-plane). As a reference example, the measurement results of the proton conductivity of the electrolyte membrane of Nafion NR211 (membrane thickness 25 μm), which is an electrolyte membrane of Dupont, are also shown. As Figure 1 shown, the proton conductivity of the electrolyte of EW560 is significantly improved compared to that of the electrolyte of EW900. The reason is that a perfluorosulfonic acid polymer with a low EW showing high proton conductivity was filled. In addition, the composite membrane filled with the electrolyte of EW900 shows lower conductivity compared to the NR211 membrane with an EW value of about 1000. Therefore, it can be said that in the case of filling the electrolyte of EW900, a composite membrane with excellent proton conductivity cannot be produced.
[0239] [Example 2]
[0240] Using the same polyolefin microporous membrane as in Example 1 and the perfluorosulfonic acid polymer of EW560, the amount of the polymer solution dropped was controlled with respect to the area of the microporous membrane, thereby producing a thinner electrolyte membrane (membrane thickness of about 7 μm). Specifically, about 0.3 ml of the polymer solution was thinly coated on a glass dish, and a polyethylene microporous membrane (thickness 6 μm, porosity 66%, size of about 35 mm × 35 mm) was gently placed thereon, dried overnight in the ambient environment, and then about 0.3 ml of the above polymer solution was further thinly coated on the polyethylene microporous membrane. By the above-described decal method, a catalyst layer was made using the above perfluorosulfonic acid polymer (EW560) as an ionomer, and a hot pressing treatment (conditions: 135 °C, 2.0 kN, 1 minute) was performed in a state where the catalyst layer was laminated with the above electrolyte membrane to produce a membrane electrode assembly (MEA) of a polymer electrolyte fuel cell.
[0241] Figure 2 For the MEA obtained as described above, the ohmic resistance was calculated based on current interruption, and the proton conductivity of the MEA was calculated. As a reference example, the electrolyte membrane Nafion NR211 (membrane thickness 25 μm) of Dupont was used. As Figure 2As shown, regarding the proton conductivity, due to the filling of a perfluorosulfonic acid polymer with high proton conductivity and low EW, and the effect of thinning the film to about one-fourth of the membrane thickness, the MEA fabricated using the polyolefin microporous membrane of the present invention exhibits higher performance compared to the case of using NR211.
[0242] Figures 3 to 5 The current density dependence of the cell voltage is shown for the MEA obtained as described above at humidities of 30%, 20%, and 10% (oxidant: oxygen or air). As a reference example, Nafion NR211 (membrane thickness 25 μm), an electrolyte membrane of Dupont, was used. In particular, as Figure 4 and Figure 5 shown, in a low humidity environment with a humidity of 20% or less, the conventional NR211 can hardly generate electricity, but the MEA fabricated using the polyolefin microporous membrane of the present invention can generate electricity up to 2 A / cm 2 (in the case of using oxygen as the oxidant), it can be seen that a new type of electrolyte membrane is obtained. It is considered that this is because by using a low EW perfluorosulfonic acid polymer (EW 560) with high proton conductivity as the ionomer in the catalyst layer, by filling the electrolyte of EW 560 in the polyolefin microporous membrane to fabricate the electrolyte membrane, and by thinning the electrolyte membrane, the water generated at the cathode can sufficiently permeate to the anode side of the electrolyte membrane, ensuring the humidity inside the electrolyte membrane.
[0243] Figure 6 The measurement results of the hydrogen crossover test are shown for the MEA (Example 2, Reference Example 1) obtained as described above. Here, after obtaining the MEA as described above, the oxidation current of hydrogen permeating through the membrane was measured under each condition of a temperature of 80 °C and a humidity of 20 - 100%, thereby conducting the hydrogen crossover test. The hydrogen supply amount on the anode side was 100 ml / minute, and the nitrogen supply amount on the cathode side was 500 ml / minute. From Figure 6 it can be seen that in the case of using the pore-filled membrane of Example 2, it was confirmed that although the membrane thickness was thinned to about one-fourth compared to the conventional NR211, the swelling of the electrolyte can still be suppressed by the polyolefin microporous membrane substrate, and the hydrogen crossover was significantly suppressed.
[0244] Figure 7 The current density dependence of the cell voltage is shown for the MEA (Example 2, Reference Example 1) obtained as described above at cell temperatures of 80 °C, 90 °C, and 100 °C. The current density was measured at a humidity of 30%. The hydrogen supply amount on the anode side was 100 ml / minute, and the oxygen supply amount on the cathode side was 500 ml / minute. From Figure 7It is known that in the conventional NR211, when the unit temperature exceeds 90 °C, the battery voltage drops sharply. This is presumably because water is discharged in the form of steam, making it difficult to humidify the membrane itself. On the other hand, when the microporous filling membrane of Example 2 is used, even in the high-temperature regions of 90 °C and 100 °C, the battery voltage hardly drops, and the membrane can be self-humidified even at high temperatures, and high power generation performance can be exhibited in the high-temperature and low-humidity regions.
[0245] [Example 3]
[0246] Except for using the perfluorosulfonic acid polymer of EW600, the operation was the same as in Example 1 to produce an electrolyte membrane (membrane thickness: 11.4 μm) containing a composite membrane.
[0247] (Evaluation of Proton Conductivity)
[0248] For the electrolyte membranes of Example 2, Example 3, Comparative Example 1, and Reference Example 1, the operation was the same as above, and the proton conductivity was evaluated by measurement by the AC impedance method (In-plane). The results are shown in Figure 8 . As Figure 8 shown, the proton conductivities of the electrolytes of EW560 and EW600 are significantly higher than those of the electrolyte of EW900.
[0249] Industrial Applicability
[0250] The electrolyte membrane of the present invention can be industrially used as a thin electrolyte membrane with high proton conductivity in electrolyte membranes advantageously used in polymer electrolyte fuel cells, water electrolysis, sodium electrolysis, etc.
Claims
1. An electrolyte membrane, comprising a composite membrane having: a polyolefin microporous membrane with an average pore diameter of 1 to 1000 nm and a porosity of 50 to 90%; and an electrolyte containing a perfluorosulfonic acid polymer with EW of 250 to 850, the electrolyte being filled in the pores of the polyolefin microporous membrane, wherein the composite membrane has a membrane thickness of 1 to 20 μm, The polyolefin microporous membrane can impregnate a solvent having a surface free energy of 33 mJ / m at 20 °C without performing either a forced filling treatment or a hydrophilic treatment based on pressurization or depressurization. 2 or more the polyolefin is a polyethylene composition obtained by mixing high molecular weight polyethylene with a weight average molecular weight of 3 million or more and low molecular weight polyethylene with a weight average molecular weight of 200,000 to 800,000 in a mass ratio of 20:80 to 80:20, and the Gurley value of the polyolefin microporous membrane measured according to JIS P8117 is 90 seconds / 100 cc or less.
2. The electrolyte membrane according to claim 1, wherein, The average pore diameter is 5 to 100 nm.
3. The electrolyte membrane according to claim 1 or 2, wherein, The porosity is 50 to 78%.
4. The electrolyte membrane according to any one of claims 1 to 3, wherein, The electrolyte contains a perfluorosulfonic acid polymer with EW of 450 to 650.
5. The electrolyte membrane according to any one of claims 1 to 4, wherein, The composite membrane has a membrane thickness of 5 to 12 μm.
6. Use of the electrolyte membrane according to any one of claims 1 to 5 as an electrolyte membrane for a polymer electrolyte fuel cell, electrolysis of water, or sodium electrolysis.
7. A method for manufacturing an electrolyte membrane, which is a method for manufacturing the electrolyte membrane according to any one of claims 1 to 5, the manufacturing method comprising the following steps: A step of impregnating a polyolefin microporous membrane with the following solution, wherein, The average pore diameter of the polyolefin microporous membrane is 1 to 1000 nm, the porosity is 50 to 90%, and it is impregnated with a solvent having a surface free energy of 33 mJ / m² at 20 °C without performing forced filling treatment and hydrophilization treatment based on pressurization or depressurization; 2 The above solution is obtained by dissolving an electrolyte containing a perfluorosulfonic acid polymer with EW of 250 to 850 in the solvent; a step of drying the polyolefin microporous membrane after the impregnation step to remove the solvent; and a step of annealing the polyolefin microporous membrane after the removal step.
Citation Information
Patent Citations
Electrolytic thin film
JP1989022932A
Thin membrane electrolyte
JP1989158051A
Polymer electrolyte composite membrane, its manufacturing method and solid polymer type fuel cell using it
JP2005166557A
Polyethylene microporous film
JP2011241361A